If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -0.33) = 2(x + 23) Reorder the terms: 6(-0.33 + x) = 2(x + 23) (-0.33 * 6 + x * 6) = 2(x + 23) (-1.98 + 6x) = 2(x + 23) Reorder the terms: -1.98 + 6x = 2(23 + x) -1.98 + 6x = (23 * 2 + x * 2) -1.98 + 6x = (46 + 2x) Solving -1.98 + 6x = 46 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -1.98 + 6x + -2x = 46 + 2x + -2x Combine like terms: 6x + -2x = 4x -1.98 + 4x = 46 + 2x + -2x Combine like terms: 2x + -2x = 0 -1.98 + 4x = 46 + 0 -1.98 + 4x = 46 Add '1.98' to each side of the equation. -1.98 + 1.98 + 4x = 46 + 1.98 Combine like terms: -1.98 + 1.98 = 0.00 0.00 + 4x = 46 + 1.98 4x = 46 + 1.98 Combine like terms: 46 + 1.98 = 47.98 4x = 47.98 Divide each side by '4'. x = 11.995 Simplifying x = 11.995
| 5+x+5x=53 | | 2x+10-3x=18 | | 12-2y^2=4 | | y=6-x/3 | | 15+3*3=6y | | 1/4X5 | | 4x^2-5=-1 | | 5x+25=135 | | -4-.1x=-6.1 | | 6.72-2a+1.68=4.5 | | -9p+2(8-p)=4p-14 | | 6.72-2a+1.68=5.4 | | 5a^2-3=77 | | 1+9x+3=6x | | 3/(x-1)*(5x-5) | | f(x)=x^2-9x+14 | | 7y+(-3)=4y-15 | | 3-4x-5x=-12 | | 10+4x=9-6x | | 3e^2x+1=15 | | .4n-7=35 | | 3x^2-9x=2x^2-2x-12 | | 2r=80 | | 3(4x-8)=.2(35x+30) | | -2x=-8/9 | | 4y-16.3=53.2 | | 14-(-8x)+5x-(-10)= | | -1.7=2.2-6.1 | | -1.7=2.2-601 | | 1-6c+7d/9c+5c-4d/6c | | 2r=98 | | 4z+3-2=-6z-7 |